The Use of Polypropylene Mesh for Revision of Failed Repair of Superficial Digital Flexor Tendon Luxation in Three Dogs - Houlton, J. E. F.; Dyce, J. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
Polypropylene mesh was used to reinforce the medial calcaneal retinaculum in three dogs which required revision of failed repair of superficial digital flexor tendon luxation. All three dogs were sound at follow-up examination three months after surgery.
Keywords: Superficial digital flexor tendon luxation; polypropylene mesh